Pengaruh Resiliensi terhadap Kepatuhan Minum Obat Oat pada Pasien TB-HIV - Indawati, Eli; Narulita, Lenny (Universitas Malahayati, 2025)
ABSTRACT About a quarter of the world's population suffers from tuberculosis infection. In Indonesia, tuberculosis is an opportunistic inflammatory disease that is generally associated with HIV. Tuberculosis and HIV remain global and Indonesian public health problems, and eradicating these diseases by 2030 is a priority. Able to identify the influence of health education on the Influence of Resilience on Compliance with OAT Medication in TB-HIV Patients. The type of research used is quantitative research and the design used is